Enforcement of Consumer Protection Rights in The Digital Market - Fajriawati, Fajriawati (Lembaga Riset Mutiara Akbar, 2023)
This research uses normative juridical research using secondary data consisting of primary and secondary legal materials, this research is descriptive analytical, namely describing or explaining precisely the form of protection and dispute resolution in trade transactions through the electronic system based on rules, norms, principles and synchronization of laws and regulations. The implementation of consumer protection rights in the digital market uses the ITE law that can solve it and Law No. 8 of 1999 concerning consumer protection against online sales of companies as their business actors carry out violations in online sales, companies are responsible for the losses they make and sacrifice consumers, based on this, defective goods and or services are not the only basis for business actor responsibility, The responsibility of business actors includes all losses experienced by consumers through the digital market.